Uso do glicosímetro portátil para a mensuração da glicemia em potros neonatos da raça mangalarga marchador - Bromerschenkel, Ingrid [UNESP]; Porfírio, Lenir Cardoso; Martins, Carla Braga (My University, 2015)
This study aimed to evaluate the use of portable blood glucose meter to measure glucose levels in neonatal foals considering how to control the results measured by laboratory test (TL) determining thereby the blood glucose values obtained by the portable blood glucose meter (GP) are in According to the Food and Drug Administration. It was used in neonatal foals of both sexes, healthy, up to 30 days of age. Blood samples were collected to measure the GP and TL in times: A: 0 to 12 hours; B: 24 to 36 hours; C: 72 hours; D: 7 days; E: and F 15 days 30 days of life. Changes in blood glucose levels obtained at TL were compared by ANOVA at 5% level of significance. For comparison of the results of the GP and TL between times A, B, C, D and F used the ttest, and the time and the Mann-Whitney test both with the 5% level of significance. The percentage variation between the results with WB and WG was obtained by the difference between the mean obtained by TL and the mean obtained by the GP. There was no difference in glycemic levels obtained by the TL between times. The average blood glucose for the neonatal period was 152,11 mg / dL. There was no difference between the results obtained by the GP and TL. The measurements obtained with GP ranged between 99 and 183 mg / dL and error rates between the 2,68 an 11,55% . There were no significant changes in blood glucose concentrations during the neonatal period. The GP demonstrated similar accuracy when TL in the determination of blood glucose levels. The GP error rate remained within the limits required by the FDA, ensuring their use for monitoring glucose levels in neonatal foals.
Use of portable glucometer for glycemia measurement in Mangalarga Marchador neonatal foals
Keywords: Blood glucose; Equine; Glucose levels